PERGESERAN PERAN DEPARTEMEN FINANCE DALAM ORGANISASI PADA TAHUN 2010 - Rosita Widjojo (Bina Ekonomi, 2003)
The rapid development of IT has removed many of the tasks which traditionally defined the finance department. Manual ledgers disappeared many years ago. Manual transaction processing is going the same way, replaced by electronic commerce. The need for financial knowledge is no longer restricted to finance. There is much greater awareness of the financial implications of decisions throughout organizations. It is a necessary part of business. Equally, business knowledge is more highly valued than technical accounting expertise. Much of the traditional finance department is moving out into the business, which means that the finance director is losing much of his or her traditional domain. Finance directors that see it as an opportunity are more likely to prosper.